2023
DOI: 10.1002/cpt.2874
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Baseline Hepatic or Renal Function and Clinical Outcomes for Patients With Non‐Small Cell Lung Cancer Treated With a PD‐1/PD‐L1 Blocking Antibody Using Real‐World and Trial Data

Abstract: Clinical trials have demonstrated the benefit of PD‐1/PD‐L1 blocking antibodies for the treatment of patients with advanced non‐small cell lung cancer (NSCLC) in defined patient populations that often exclude patients with moderate or severe hepatic or renal impairment. We assessed the association between overall survival (OS) and baseline organ function in patients with advanced NSCLC treated with PD‐1/PD‐L1 blocking antibodies in real‐world data (RWD; patient‐level data from electronic health records) and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…2 At the same time, a revolution in real-world data (RWD) has been emerging from the rapid digitization of electronic health records, with numerous industry and academic analyses of patient data, allowing for improved understanding of patient outcomes outside of clinical trials. [3][4][5] In the accompanying article by Leshem et al, 6 the investigators used two separate databases to evaluate the effect of diabetes on outcomes for patients with non-small cell lung cancer being treated with immune checkpoint inhibitors, either alone or in combination with chemotherapy. The investigators found a difference in survival outcomes when comparing diabetic patients to nondiabetic patients.…”
Section: Signal Detection In Real-world Data and Confirmation In Clin...mentioning
confidence: 99%
“…2 At the same time, a revolution in real-world data (RWD) has been emerging from the rapid digitization of electronic health records, with numerous industry and academic analyses of patient data, allowing for improved understanding of patient outcomes outside of clinical trials. [3][4][5] In the accompanying article by Leshem et al, 6 the investigators used two separate databases to evaluate the effect of diabetes on outcomes for patients with non-small cell lung cancer being treated with immune checkpoint inhibitors, either alone or in combination with chemotherapy. The investigators found a difference in survival outcomes when comparing diabetic patients to nondiabetic patients.…”
Section: Signal Detection In Real-world Data and Confirmation In Clin...mentioning
confidence: 99%
“…In one collaborative research project, both RWD and pooled clinical trial data were used to assess the association between OS and baseline organ function in patients with advanced NSCLC treated with PD‐1/PD‐L1 blocking antibodies. 26 Both RWD and clinical trial data suggested that baseline renal impairment did not appear to be associated with OS, while patients with baseline liver impairment had shorter OS. In addition, RWD included patients over a broader range of renal and hepatic function than was enrolled in clinical trials.…”
Section: Introductory Lecturesmentioning
confidence: 99%
“…OCP has also been working on many collaborative research projects to identify where RWE can be most helpful and to develop best practices to advance RWE for clinical pharmacology. In one collaborative research project, both RWD and pooled clinical trial data were used to assess the association between OS and baseline organ function in patients with advanced NSCLC treated with PD‐1/PD‐L1 blocking antibodies 26 . Both RWD and clinical trial data suggested that baseline renal impairment did not appear to be associated with OS, while patients with baseline liver impairment had shorter OS.…”
Section: Introductory Lecturesmentioning
confidence: 99%
“…Thus, when patients ask the question as to whether or not a given approved therapy is right for them, it should be possible to find data from similar patients with the same conditions to determine the answer. Other efforts have shown the benefits of immunotherapy to specific subpopulations, such as in patients with melanoma or lung cancer with co-occurring kidney or liver dysfunction, or for patients with certain rare comorbid conditions . When there are multiple choices, this kind of information can be particularly important for patients and clinicians when determining the best available therapy.…”
mentioning
confidence: 99%